The Resilient History of Palestinian Resistance and Its Impact on the Emergence of Converts to Islam in the West - Rabbani, Athiya Nasywa; Hasbullah, Moeflich (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This research examines the history of Palestinian resistance and its impact on the emergence of converts to Islam in the West, using historical research methods that include heuristics, source criticism, interpretation, and historiography. This research focuses on the development of Palestinian resistance, their resilience that garnered global sympathy, and the case study of Lauren Booth. The Palestinian-Israeli conflict, which originated from the issuance of the Balfour Declaration in the early 20th century, gave rise to various forms of Palestinian resistance, from the Intifada to Toufan Al-Aqsa, showcasing extraordinary physical and spiritual resilience. This resilience successfully evoked global sympathy, including inspiring Western communities to embrace Islam. Among them was Lauren Booth, a British journalist who converted to Islam.